Dietary exposure to mycotoxins through fruits juice consumption - D. Carballo (Revista de Toxicología, 2018)
A study on fruit juice products (apple, pineapple, apricot, orange and pear) was carried out to determine the natural occurrence of fifteen mycotoxins by gas chromatography coupled to tandem mass spectrometry (MS/MS). A developed multi-mycotoxin procedure was carried out by dispersive liquid-liquid microextraction (DLLME). 36% of the analyzed samples presented mycotoxin contamination. PAT was detected in orange, apple, mixed fruits and pineapple juices with prevalence of 86%, 60%, 29%, 14% at meanconcentrations of 34.57 µg/L, 33.41 µg/L, 8.59 µg/L, 8.02 µg/L, respectively. One orange juice sample, exceeded the maximum level (ML) established by EU for PAT (50 µg/L). HT-2 toxin was found in mixed juice (43%) at mean level of 22.38 µg/L. Overall no toxicological concern was associated to mycotoxins exposure for children and adult population and the results obtained highlight the necessity for rigorous monitoring studies on HT-2 in fruit juice.